Understanding the Intersection of culture: The way forward of higher education sector in strengthening regional cooperation - Abdul Rahman, Shukran; Alwi, Azlin (ACADEMY OF IRMBR International Research in Management & Business Realities, 2017)
The contribution of Malaysia to the international society was evident with the implementation of Cambodia, Laos, Myanmar, and Vietnam initiatives and Malaysia Global Outreach programs. Though efforts had been put in place to create an ecosystem that nurtured cooperation among higher learning institutions in the region, little has been done to study the extent to which the different culture has been taken into account in the programs conducted. This paper discusses the approaches taken by HLIs in conducting educational programs for participants from different cultural background; and highlights the extent to which the program providers addressed the intersection of culture before designing and implementing the programs.